A Case Study on Hemorrhage Due to Cerebrovascular Disease (Journal of Nobel Medical College, 2024)
Cerebrovascular disease includes some of the most common and devastating disorders: ischemic and hemorrhagic stroke. Stroke is the second leading cause of death worldwide, with 6.2 million dying from stroke in 2015, an increase of 830,000 since 2000. Stroke remains the most common disabling disease worldwide and in many forms is preventable. A stroke, or cerebrovascular accident, is defined as an abrupt onset of a neurologic deficit that is attributable to the focal vascular cause. Thus, the definition of stroke is clinical, and laboratory studies including brain imaging are used to support the diagnosis.